2019
DOI: 10.1177/1836939119832084
|View full text |Cite
|
Sign up to set email alerts
|

Digital play in young children’s numeracy learning

Abstract: Advances in technology have seen a proliferation of touch-screen interfaces available to young children. These screens have changed the way in which young children engage with digital technology; with increased exposure and use, it raises debates about the suitability of integrating digital technology within early childhood settings. There are limited empirical studies that investigate the appropriateness of emergent digital technology within the field of early childhood. Based upon the TPACK model, this timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
(54 reference statements)
0
6
0
1
Order By: Relevance
“…In fact, regardless of the original modality children practiced the task on (2D or 3D), all children improved in the final problemsolving task (Huber et al, 2016). Further, evaluations of specific math apps have also found mostly positive results (e.g., Stiles and Louie, 2016;Disney et al, 2019). For example, Schacter and Jo (2016) demonstrated that preschoolers can learn math concepts from a math-oriented game (Math Shelf) on a tablet.…”
Section: Science Technology Engineering and Mathmentioning
confidence: 99%
“…In fact, regardless of the original modality children practiced the task on (2D or 3D), all children improved in the final problemsolving task (Huber et al, 2016). Further, evaluations of specific math apps have also found mostly positive results (e.g., Stiles and Louie, 2016;Disney et al, 2019). For example, Schacter and Jo (2016) demonstrated that preschoolers can learn math concepts from a math-oriented game (Math Shelf) on a tablet.…”
Section: Science Technology Engineering and Mathmentioning
confidence: 99%
“…und richtet sich gezielt an Kinder zwischen 3-6, meist aber zwischen 5-6 Jahren. Disney et al (2019) untersuchten die Rechenfertigkeiten von 3-4-jährigen Kindern. 80 Kinder nutzten in der Studie ausgewählte gestenbasierte Rechen-Apps auf Tablets.…”
Section: Mediennutzung Und Medieneinsatz Im Kontext Der Frühen Kindheitunclassified
“…Previous studies have primarily concentrated on learning Mathematic through play. Disney et al (2019) studied the integration of digital technology within early childhood settings. Their analysis revealed that young children's numeracy learning outcomes were improved after they used the applications via iPad technologies.…”
Section: Learning Outcomes (33 Articles) Mathematics (11 Articles)mentioning
confidence: 99%